REFERENCES TO PRACTICE IN LATE 19TH AND EARLY 20TH CENTURY SOURCES - Ergashev Alimardon (Web of Journals Publishing, 2024)
In this article, the words related to amal-mansab used in Uzbek texts at the end of the 19th and the beginning of the 20th century are given with an explanation. In the article, the level of use of such words and options are given.
Keywords: Rank, khanate, king, prince, official, lower rank, higher rank.